Giant panda׳s tooth enamel: Structure, mechanical behavior and toughening mechanisms under indentation. (December 2016) - Weng, Z.Y.; Liu, Z.Q.; Ritchie, R.O.; Jiao, D.; Li, D.S.; Wu, H.L.; Deng, L.H.; Zhang, Z.F.
Abstract: The giant panda׳s teeth possess remarkable load-bearing capacity and damage resistance for masticating bamboos. In this study, the hierarchical structure and mechanical behavior of the giant panda׳s tooth enamel were investigated under indentation. The effects of loading orientation and location on mechanical properties of the enamel were clarified and the evolution of damage in the enamel under increasing load evaluated. The nature of the damage, both at and beneath the indentation surfaces, and the underlying toughening mechanisms were explored. Indentation cracks invariably were seen to propagate along the internal interfaces, specifically the sheaths between enamel rods, and multiple extrinsic toughening mechanisms, e.g., crack deflection/twisting and uncracked-ligament bridging, were active to shield the tips of cracks from the applied stress. The giant panda׳s tooth enamel is analogous to human enamel in its mechanical properties, yet it has superior hardness and Young׳s modulus but inferior toughness as compared to the bamboo that pandas primarily feed on, highlighting the critical roles of the integration of underlying tissues in the entire tooth and the highly hydrated state of bamboo foods. Our objective is that this study can aid the understanding of the structure-mechanical property relations in the tooth enamel of mammals and further provide some insight on the food habits of the giant pandas. Graphical abstract: Highlights: Giant panda׳s tooth enamel has a hierarchical structure with chemical gradient. The mechanical properties depend on both the structural orientation and location. Indentation cracks tend to propagate along sheaths or boundaries of HAP fibers. Multiple extrinsic toughening mechanisms act to shield cracks from applied stress. Enamel has superior hardness and modulus but inferior toughness compared to bamboo.